Clinical features of the pulmonary tuberculosis course combined with different diabetes mellitus types in the Zaporizhzhia region - Raznatovska, O. M.; Bobrovnycha-Dvizova, Yu. M. (Zaporozhye Medical Journal, 2017)
The purpose of the work – to determine the clinical features of the pulmonary tuberculosis course combined with different types of diabetes mellitus (DM) in the Zaporizhzhia region for the further development of the differentiated approach to the management of these patients. Materials and methods of research. The study included 49 patients with pulmonary tuberculosis who were in inpatient treatment in the Departments of Clinical site of the tuberculosis and pulmonology department of the ZSMU in the "Zaporizhzhia Regional Clinical TB Dispensary" Municipal institution. The patients were divided into 2 groups: a group of 1 – 31 patients with pulmonary tuberculosis combined with the 1 type DM course, a group of 2 to 18 patients with pulmonary tuberculosis combined with the 2 type DM course. The outcomes of the study were processed by modern analysis methods on a personal computer using the statistical package of the Statistica® for Windows 6.0 (StatSoft Inc., No. AXXR712 D833214FAN5) license program. Results. In tuberculosis patients with the combined type 1 DM course, regardless of sex, young people aged 31–40 years significantly predominate, and with type 2 diabetes – men over 40 years of age. In tuberculosis patients with the combined type 1 DM course, the infiltrative form of tuberculosis is 1.5 times more frequent than that of type 2 DM. In the case of the combined type 1 DM course, the tendency towards the infiltrative form predominance is determined, but compared to type 1 diabetes, the disseminated form is 10.4 times predominant. The vast number of patients in both groups are patients with bacterial excretion, and on discharge from hospital, the number of patients with bacterial excretion with the combined type 2 DM course remains 1.7 times larger. Regardless of the concomitant DM type, the vast majority of patients have a destructive process in the lungs with a predominance of cavities up to 4 cm in diameter, regardless of their number. Despite the fact that regardless of the concomitant DM type, the average time of the destructions healing in both groups is almost equal (5 months), in patients with type 2 DM there is a tendency to 2 times more frequent healing of destructions. Type 1 DM is of the predominantly severe and moderate severity in the subcompensation stage, and type 2 diabetes in almost all patients is of moderate severity with a tendency to the predominance of the decompensation stage. Regardless of the concomitant DM type, in the half of patients in the setting of the TB course combined with DM, the concomitant conditions are diagnosed: hypertonic disease and pulmonary heart failure in patients with the combined type 2 diabetes are prevalent in comparison with the patients with type 1 DM, where there is a tendency to increase in the pulmonary heart failure and hepatitis incidence. In TB patients, the complications of DM develop 1.3 times more frequent with type 1 than with type 2, which are manifested predominantly by diabetic vascular disorders, namely, retinal angiopathy and lower extremity angiopathy and ketoacidosis. And complications of type 2 diabetes are diabetic: vascular disorders, encephalopathy and diabetic foot. Regardless of the concomitant diabetes type, the incidence of adverse reactions to antimycobacterial drugs in cases of resistant tuberculosis is 37.5 % in patients with the combined type 1 DM and 44.4 % with the combined type 2 DM. In cases of tuberculosis with the combined type 2 DM, 5 times more patients have been provided with the palliative therapy. Conclusions. The course of tuberculosis largely depends on the type of diabetes. When combined with type 1 diabetes, the more unfavorable and severe course of both diseases is determined, while in combination with type 2 diabetes, on the contrary.